Two New Species of simulium (Gomphostilbia) (Diptera: Simuliidae) from Peninsular malaysia - Takaoka, H.; Sofian-Azirun, Mohd; Hashim, R.; Ya'cob, Z.; Chen, C.D. (2012)
Two new species of black flies, Simulium (Gomphostilbia) terengganuense sp. nov. and Simulium (Gomphostilbia) aziruni sp. nov. (Diptera: Simuliidae), are described on the basis of reared adult, pupal, and larval specimens collected from Peninsular Malaysia. Both species are placed in the batoense species-group within the subgenus Gomphostilbia, one of two dominant subgenera of the genus Simulium in Peninsular Malaysia as well as in the Oriental Region. Strikingly, three morphological characteristics that rarely occur in the subgenus Gomphostilbia are found in these two new species: the very narrow female frons and the mushroom-like pupal terminal hooks in S. (G.) terengganuense sp. nov. and the pupal gill composed of an inflated horn-like structure and eight slender filaments in S. (G.) aziruni sp. nov.